Productivity of the use of energy resources in Nicaraguan electricity market agents with cogeneration systems - Blanco-Orozco, Napoleón Vicente (2018)
In this paper, the productivity of the use of sugarcane bagasse and petroleum derivatives for the generation of electric energy was evaluated using the DEAP and Malmquist indexes. The results show that the total productivity of the factors of the use of bagasse to generate electrical energy registers an interannual decrease. In the case of the use of petroleum derivatives to generate energy, the total factor productivity in general average registered deterioration; however, some of the thermal plants studied registered a growth rate. This means that there is an opportunity for the review of production processes to increase the productivity of the use of bagasse and that oil derivatives are being managed with greater productivity to generate electricity.